The Effect of Sweet Bee Venom Pharmacopuncture(SBVP) on Cancer-Related Pain : A Randomized Controlled Trial and Double Blinded - Pilot study - Hwa-Seung Yoo; Jung-Sun Kim (Korean Pharmacopuncture Institute, 2008)
Objectives : To investigate the therapeutic effects of SBVP in the treatment of patients with cancer-related pain. Design : A prospective randomized, double-blind, placebo-controlled study of SBVP. Setting : The study was conducted at the East West Cancer Center of Daejeon University Dunsan Oriental Hospital from March 1, 2007 to June 20, 2007. Patients : 11 patients diagnosed with cancer-related pain of over 3rd degree on the Numeric Rating Scale(NRS)(0, no pain at all, 10, worst pain imaginable) were entered into a double-blind, placebo-controlled trial of SBVP. They were randomized into Groups A and B(SBVP and control group, respectively) using the table of random sampling numbers and never informed of their affiliation by the coordinator. 5 of 6 patients in Group A and 4 of 5 patients in Group B completed the clinical trial. Intervention : SBVP(1ml/day) for group A and Normal Saline Placebo(1ml/day) for group B was injected into the abdomen acupoint, Zhong Wan(CV 12). The treatment was administered daily for five days. Outcome Measures : Degree of cancer-related pain was measured using the Numeric Rating Scale(NRS) before and after each treatment for "Pain right now" and "Average pain in last 24 hours". Statistical Analysis : regarding variations in NRS was carried out by applying t-tests(independent sample t-test and paired sample ttest) nd Wilcoxon signed rank test with level of significance at 5%. Results : fferences in NRS of "Pain right now" for the two groups were statistically significant. The mean improvement point of SBVP was significantly higher than the control group(2.48°±1.52 vs 0.97°±1.88, p<0.05). Differences in average pain score before and after treatment in SBVP group were also significant(5.13°±1.77 vs 2.65°±0.67, p<0.05) compared with control group. The two groups showed no significant differences for long term effects in "Average pain in last 24 hours." Conclusion : Although further study will be needed on the large scale, SBVP shows potential as an effective treatment for immediate relief of cancer-related pain.